Current treatment options for allergic rhinitis: a review - Swain, Santosh Kumar; Singh, Vasudha (International Journal of Research in Medical Sciences, 2023)
Allergic rhinitis (AR) is an immunoglobulin E-mediated inflammatory reaction in the nasal mucosa caused by inhaled allergens such as dust, pollen, mold, or animal dander. AR is a common chronic disease that is often ignored, misdiagnosed, and/or mistreated. Clinically, AR is characterized by four major symptoms such as rhinorrhea, sneezing, nasal itching, and nasal congestion. It can be associated with certain co-morbid conditions like asthma and nasal polyposis. AR is diagnosed by taking proper history taking, nasal examination, and allergy tests. A proper understanding of the pathophysiology of AR can lead to improved treatment of this disorder. The treatment for AR should target symptoms to improve the quality of life for patients. Undertreatment of AR often impairs quality of life. The important concern in the treatment of AR is the patient’s adherence to the treatment. Novel treatments are needed for cheaper, early, better, and more permanent symptom resolution in AR. Evidence-based guidelines for AR treatment are helpful to improve disease control. The treatment of AR includes avoidance of relevant allergens, appropriate pharmacotherapy, immunotherapy, patient education, and follow-up. Intranasal corticosteroids are the most effective modality of treatment for AR. This review article discusses details of current treatment options for AR.